METHOD OF REVERSE NONEQUILIBRIUM POSITIONAL ENCODING WITH BI-DIRECTIONAL LEXICOGRAPHY - Barannik, Valerii (Science-based technologies, 2025)
The article substantiates the existence of a limiting factor: the insufficient performance of modern wireless information and communication systems (WICS) to meet the requirements of applied operational concepts. This indicates the need for further development of video data compression technologies. Conditionally, all compression methods can be divided into two types. These types differ in their use of redundancy reduction technologies based on a psycho-content model. Both types of methods are generally used together in complex compression systems, complementing each other. This is especially relevant when high practical compression levels are required for video images with high informational density. Under such conditions, the psycho-content model enables compression within certain bounds. Additional compression beyond these limits can be achieved using methods of the second type, which take into account structural-content and statistical-content characteristics of video images. This highlights the need to further improve psycho-independent methods. Promising representatives of the second type are structural-positional compression technologies, with Nonequilibrium Positional (NEP) encoding being the foundational method. NEP encoding methods have demonstrated effectiveness in compressing video segments with varying levels of informational content. A key feature of such methods is their dependence on the configuration of the detection process for structural-positional dependencies in dynamically changing segment lengths. Consequently, a unidirectional approach to constructing lexicographic rules reveals certain shortcomings. Therefore, it is proposed to develop NEP encoding methods that incorporate a bi-directional lexicographic vector. The article outlines the main stages in developing a reverse NEP encoding method that enhances the weight of lower-order elements in a two-dimensional NEP space with bi-directional lexicography. This approach also considers: local structural-statistical patterns during element value indexing within operational ranges; localization of the upper bounds of dynamic element ranges by simultaneously accounting for two-dimensional structural constraints along rows and columns of the transform domain.